What links obesity to cancer? - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2005)
The predominant cancers associated with obesity include breast, endometrial and prostate cancer which all have a hormonal basis. Several studies have shown that obesity also increases the risk for cancers of the colon, oesophagus (adenocarcinoma), pancreas, gall bladder, liver, cervix, ovaries, kidney, as well as Hodgkin's disease and non-Hodgkin's lymphoma. The mechanism of increased cancer risk in obese populations is unclear, but nutritional and dietary factors, and lack of exercise may have a role. The conversion of androstenedione, which is secreted by the adrenal gland, into oestrone by aromatase in adipose tissue stroma provides an important source of oestrogen for postmenopausal women. Leptin may be a possible link between Western lifestyle and the transition from premalignant lesions to overt cancer through the induction of tumour angiogenesis. Insulin and IGF-I may be the biological mediators of cell growth. The increased release of cytokines by the adipocyte may play a role in the inflammatory state associated with obesity.
Keywords: obesity; diet; exercise; sex hormones; insulin; leptin; IGF-1; VEGF; GROWTH-FACTOR I; BREAST-CANCER; COLORECTAL-CANCER; PHYSICAL-ACTIVITY; DIETARY-FAT; BODY-MASS; RISK; HORMONES; INSULIN; HYPERTENSION